2020
DOI: 10.1038/s41598-020-77651-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and novel photoluminescence properties of the self-supporting nanoporous InP thin films

Abstract: Self-supporting nanoporous InP membranes are prepared by electrochemical etching, and are then first transferred to highly reflective (> 96%) mesoporous GaN (MP-GaN) distributed Bragg reflector (DBR) or quartz substrate. By the modulation of bandgap, the nanoporous InP samples show a strong photoluminescence (PL) peak at 541.2 nm due to the quantum size effect of the nanoporous InP structure. Compared to the nanoporous InP membrane with quartz substrate, the nanoporous membrane transferred to DBR shows a tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[5,6] Furthermore, gallium arsenide (GaAs), indium phosphide, and other single-crystal semiconductor films are model materials in modern microelectronic industries. [7,8] Beyond these canonical systems, there is high demand to expand these methods to preparing single crystal thin films of emerging semiconductors such as halide perovskite ABX 3 materials (e.g., MAPbX 3 , FAPbX 3 and CsPbX 3 , where MA + is CH 3 NH 3 emitting properties [30,31] and is more stable than MAPbX 3 , [32] leading to applications in photodetectors and LED devices. [33,34] For example, Li et al demonstrated that controlling surface ligand density on CsPbBr 3 perovskite quantum dots can lead to a 50-fold improvement external quantum efficiency in lightemitting diodes incorporating the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,6] Furthermore, gallium arsenide (GaAs), indium phosphide, and other single-crystal semiconductor films are model materials in modern microelectronic industries. [7,8] Beyond these canonical systems, there is high demand to expand these methods to preparing single crystal thin films of emerging semiconductors such as halide perovskite ABX 3 materials (e.g., MAPbX 3 , FAPbX 3 and CsPbX 3 , where MA + is CH 3 NH 3 emitting properties [30,31] and is more stable than MAPbX 3 , [32] leading to applications in photodetectors and LED devices. [33,34] For example, Li et al demonstrated that controlling surface ligand density on CsPbBr 3 perovskite quantum dots can lead to a 50-fold improvement external quantum efficiency in lightemitting diodes incorporating the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5,6 ] Furthermore, gallium arsenide (GaAs), indium phosphide, and other single‐crystal semiconductor films are model materials in modern microelectronic industries. [ 7,8 ]…”
Section: Introductionmentioning
confidence: 99%